Ordinals are not as easy as one, two, three: The acquisition of cardinals and ordinals in Dutch. (2nd October 2018) - Meyer, Caitlin; Barbiers, Sjef; Weerman, Fred
ABSTRACT: This study argues that the pattern and timing of ordinal acquisition differs substantially from that of cardinals and is influenced by different language-specific factors, such as (ir)regular ordinal morphology, superlative morphology, and the singular-plural distinction. We discuss data from a Give X task (Wynn 1992) administered to 77 Dutch monolinguals (2;11–6;04) that support a so-called knower-level acquisition pattern (e.g., Le Corre & Carey 2007) for Dutch cardinals but show a more complex picture for ordinals, which are acquired around the time a child masters the necessary counting principles and becomes a CP (cardinal principle) knower. Not only is the tiered pattern absent in regular low ordinals, we also see that it takes time for children to link drie 'three' to irregular derde 'third.' We take this as evidence that ordinals are acquired via rules, rather than being stored lexically one by one.